Accelerated and long term stability study of Pfs25-EPA conjugates adjuvanted with Alhydrogel®. Issue 24 (31st May 2017) - Zhu, Daming; Wu, Yimin; McClellan, Holly; Dai, Weili; Rausch, Kelly; Jones, Dominique; Aebig, Joan; Barnafo, Emma; Butler, Brandi; Lambert, Lynn; Narum, David L.; Duffy, Patrick E.
Abstract: Pfs25, a Plasmodium falciparum surface protein expressed during zygote and ookinete stages in infected mosquitoes, is a lead transmission-blocking vaccine candidate against falciparum malaria. To enhance immunogenicity, recombinant Pfs25 was chemically conjugated to recombinant nontoxic Pseudomonas aeruginosa ExoProtein A (rEPA) in conformance with current good manufacturing practices (cGMP), and formulated with the alum adjuvant Alhydrogel. In order to meet the regulatory requirements for a phase 1 human clinical trial, the vaccine product was extensively evaluated for stability at an initial time point and through the clinical trial period annually. Because basic quality control methods to characterize alum-based vaccines remain unavailable, a thermal forced degradation study was performed prior to the initial evaluation to identify the methods suitable to detect the quality of vaccine formulations. Our results show that the vaccine product Pfs25-EPA formulated on Alhydrogel is in conformance with regulatory guidelines and suitable for human trials.